MicroFranchising creating wealth at the bottom of the pyramid - Fairbourne, Jason S., 1973-; Gibson, Stephen W. (Stephen Wallace), 1941-; Dyer, W. Gibb, 1954-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2007)
This unique book provides an overview of the need to alleviate poverty and what methods have been used in the past to do so (e.g. microcredit). It then introduces the concept of the microfranchise and discusses how this business model can be used in poverty alleviation. Different models of microfranchising are reviewed and specific case studies highlighted to show how it has worked in different parts of the world. The book concludes with a discussion of the advantages as well as the potential problems and pitfalls that accompany microfranchising.
Why microfranchising is needed now : introduction and book overview / Jason S. Fairbourne -- Microfranchising : the next step on the development ladder / Stephen W. Gibson -- The informal economy and microfranchising / Michael Henriques and Mathias Herr -- Current international development tools to combat poverty / Warner Woodworth -- Opportunities for partnership : how microfinance and microfranchising compliment each. other / John Hatch. -- Microfranchising and the base of the pyramid / Molly Hoyt and Eliot Jamison -- Microfranchise business models / Kirk Magleby -- Honey Care Africa / Farouk Jiwa -- Franchising healthcare for Kenya : the HealthStore Foundation model / Michelle Fertig and Herc Tzaras -- Vodacom Community Services : rural telephone access for South Africa / Lisa Jones Christensen, Jennifer (Reck) Van Kirk and Brad Wood -- Scojo Foundation / Jordan Kassalow, Graham Macmillan, and Neil Blumenthal -- Microfranchise funding / Naoko Felder-Kuzu -- The future of microfranchising : opportunities and challenges / W. Gibb Dyer, Jr.
Includes bibliographical references and index.
Keywords: Franchises (Retail trade); Small business; Poverty; Poverty -- Prevention; Electronic books